Over-expression of CsGSTU promotes tolerance to the herbicide alachlor and resistance to Pseudomonas syringae pv. tabaci in transgenic tobacco - L. Lo Cicero; V. Catara; C. P. Strano; P. Bella; P. Madesis; A. R. Lo Piero (Biologia Plantarum, 2017)
Glutathione transferases (GSTs) mainly catalyze the nucleophilic addition of glutathione to a large variety of hydrophobic molecules participating to the vacuole compartmentalization of many toxic compounds. In this work, the putative tolerance of transgenic tobacco plants over-expressing CsGSTU genes towards the chloroacetanilide herbicide alachlor was investigated. Our results show that the treatment with 0.0075 mg cm-3 of alachlor strongly affects the growth of both wild type and transformed tobacco seedlings with the sole exception of the transgenic lines overexpressing CsGSTU2 isoform that are barely influenced by herbicide treatment. In order to correlate the in planta studies with enzyme properties, recombinant CsGSTs were in vitro expressed and tested for GST activity using alachlor as substrate. The recombinant GSTU2 enzyme was twice more active than GSTU1 in conjugating alachlor to GSH thus indicating that CsGSTU2 might play a crucial role in the plant defense against the herbicide. Moreover, as a consequence of the infiltration with a bacterial suspension of the P. syringae pv. tabaci, transgenic tobacco plants but not wild type plants bestowed the capability to limit toxic metabolite diffusion through plant tissues as indicated by the absence of chlorotic halos formation. Consequently, the transgenic tobacco plants described in the present study might be utilized for phytoremediation of residual xenobiotics in the environment and might represent a model for engineering plants that resist to pathogen attack.